Praktik Keliru Doktrin Judicial Activism dalam Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 - Dea Ananda; Herdiansyah Hamzah; Poppilea Erwinta (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to determine the requirements for applying the Doctrine of Judicial Activism in judicial decision-making and the errors contained in ConstitutionaL Court Decision Number 90/PUU-XXI of 2023.The research method used in this paper is a doctrinal approach. This research was conducted by reviewing literature such as previous research, journal references, laws and regulations, court decisions, reference books and research journals, and various oth er supporting sources. The results of this study answer two research questions. The research findings demonstrate how the doctrine of Judicial Activism operates effectively, in accordance with established requirements, and that the Constitutional Court must adhere to these requi rements and not rely solely on its own authority in making decisions. However, this research demonstrates that Constitutional Court Decision Number 90/PUU-XXI of 2023 erroneously applies the doctrine of Judicial Activism to the authority held by judges. This research also contributes to a deeper understanding of the limitations of the Constitutional Court's authority in material review, as well as the implications of applying this doctrine to the judicial process in Indonesia. Therefore, the results of this research are expected to serve as a reference for further legal studies on constitutional review in Indonesia.